A positive policy? Corporate perspectives on redundancy and outplacement - Doherty, Noeleen; Tyson, Shaun; Viney, Claire (Emerald Group Publishing Limited, 1993)
The management of the job-loss situation is becoming of central importance to top management and human resource executives in the current climate of redundancy. The current nature of severance packages and the provision of outplacement may be interpreted as a move towards normative practices within the policy making of many UK organizations. Reports on the results of a recent survey of over 600 UK organizations. The survey covered organizational perspectives on redundancies and the use of outplacement in the event of redundancy. The results indicated a change in corporate values in the 1990s. There appeared to be a move towards normative practices in the management of redundancy and in particular in the use of outplacement as a moderator of the potentially detrimental impact of the redundancy situation.